Both angel and devil: The suppressing effect of transformational leadership on proactive employee's career satisfaction. (August 2017) - Li, Jiannan; Yuan, Bocong
Highlights: Proactive personality positively predicted career satisfaction. Bright side of transformational leadership had the direct positive moderation effect. The dark side had the indirect negative moderation effect through LLX. Opposite effects of two sides counteracting each other leads to suppressing effect. Abstract: This paper empirically examined the effect of hotel employees' proactive personality on career satisfaction and the suppressing moderation effect of transformational leadership on this relationship. Results of multisource and time lagged data from 75 team supervisors and 464 subordinates showed that proactive personality positively predicted career satisfaction. Moreover, the bright side of transformational leadership had direct positive moderation effect on the relationship between proactive personality and career satisfaction, while the dark side had indirect negative moderation effect on such relationship through its influence on LLX (i.e., leader–leader exchange). With the opposite effects of these two sides counteracting each other, the total moderation effect of transformational leadership became nonsignificant, that is, the suppressing effect happened to transformational leadership. Theoretical and practical implications of these findings were discussed.